Building BRIDGES: A Design Experiment to Improve Reading and United States History Knowledge of Poor Readers in Eighth Grade. (July 2015) - O'Connor, Rollanda E.; Beach, Kristen D.; Sanchez, Victoria M.; Bocian, Kathleen M.; Flynn, Lindsay J.
We tested the effects of teaching reading skills through U.S. history content for 38 eighth-grade poor readers whose reading ability ranged from second- to fourth-grade levels. Half of the students received special education services, and half of the students were English language learners. Students were taught to decode multisyllabic words, learn meanings of academic words, and identify cause-and-effect relationships. They used easy levels of history text and then bridged into more difficult text accounts of the same events. Results showed gains in performance across each cycle in each reading component. Comparisons between students in the intervention and their typically developing peers showed stronger gains for intervention students in vocabulary and comprehension strategies. Students with disabilities who received instruction in causes and effects of historical events scored similarly to typical readers in their general education history classes.